Laparoscopic peritoneal lavage in patients with Hinchey III acute diverticulitis attended at a private clinic in Lima - Túpac-Sulca, Oscar Edú (2023)
Diverticulosis is defined as the presence of diverticula in the intestine, when these diverticula become inflamed diverticulitis occurs, but this complication happens in less than 5% of these patients. Surgical treatment is indicated in complicated diverticulitis cases. Traditionally, the Hartmann procedure is carried out in patients with Hinchey III and IV acute diverticulitis. Currently, individualized surgical procedures are indicated in patients with non-fecal purulent peritonitis with laparoscopic peritoneal lavage as an optional choice. Objective: To report the results of laparoscopic peritoneal lavage in four patients with Hinchey III acute diverticulitis performed at a private clinic. Methods: Case series for which a review of patient clinical files was done. Results: No post-operative complications or mortality was found. Conclusions: based on authors judge, laparoscopic peritoneal lavage leads to an adequate post-operative evolution resulting in better quality of life.